MATERIAL PROCESS IN DRAMA SERIES â€œ13 REASONS WHYâ€ - Sylvina Arisyi Febriari; Ariffuddin Ariffuddin (PRIMACY Journal of English Education and Literacy, 2022)
The objectives of the research were to determine the types of Material Process used in 13 Reason Why film transcript in Jay Asher movie and to find out the most dominant material process type applied in 13 Reason Why film transcript in analyzing Jay Asher movie. The research was conducted by using descriptive qualitative design. The data of this research were utterances based on the transcript of 13 Reason Why film transcript that were downloaded from https://13reasonswhy.fandom.com/wiki/Tape_1,_Side_A/Transcript\. The data was analyzed by using Systemic Functional Linguistics based on Halliday. The result of this research was: (1) there were four types of Material Process in the transcript of 13 Reason Why film transcript, namely: Process of Doing (247 utterances or 76,23%), Process of Creating (50 utterances or 15,43%), Process of Happening (21 utterances or 6,48%), and Abstract Process (6 utterances or 1,85%). The most dominant type of Material Process applied in 13 Reasons Why transcript is Process of Doing (247 utterances with percentage 76,23%).